1998
DOI: 10.1042/bj3340625
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-phosphorylation-dependent and Rho-protein-mediated control of cellular phosphatidylinositol 4,5-bisphosphate levels

Abstract: The polyphosphoinositide PtdIns(4,5)P # , best known as a substrate for phospholipase C isozymes, has recently been recognized to be involved in a variety of other cellular processes. The aim of this study was to examine whether the cellular levels of this versatile phospholipid are controlled by tyrosine phosphorylation. The studies were performed in human embryonic kidney (HEK)-293 cells stably expressing the M $ muscarinic acetylcholine receptor. Inhibition of tyrosine phosphatases by pervanadate induced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
0
25
1
Order By: Relevance
“…This effect could be explained by the ability of Src to modulate the amount of PLC substrate, PIP 2 . It has been previously reported that tyrosine kinase inhibition leads to a rapid decrease of cellular PIP 2 levels in HEK-293 cells (15). The resynthesis of PIP 2 occurs in a sustained fashion in nonstimulated cells and very rapidly after PLC hydrolysis (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect could be explained by the ability of Src to modulate the amount of PLC substrate, PIP 2 . It has been previously reported that tyrosine kinase inhibition leads to a rapid decrease of cellular PIP 2 levels in HEK-293 cells (15). The resynthesis of PIP 2 occurs in a sustained fashion in nonstimulated cells and very rapidly after PLC hydrolysis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Inositol phosphate production reflects PLC activity, which in turn depends on the availability of the substrate PIP 2 (5). Because tyrosine kinase inhibition may significantly reduce levels of PIP 2 (15), amounts of PIP 2 in control and PP1 (10 M)-treated cells were measured. No effect of PP1 was detected when the whole pool of phosphoinositides was assayed (data not shown).…”
Section: Src Activity Regulates 5-ht-induced Asm Cell Contractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large clostridial toxins, such as Clostridium difficile toxin B and toxin A, also block PLD activity induced by PMA, or GTP [S] in vitro, probably by reducing PI4-P 5-kinase activity and decreasing PIP 2 level (Schmidt et al, 1996a;Rümenapp et al, 1998). Indeed, PLD, which contains a PH (pleckstrin homology) domain and a PX (Phox homology) domain, as well as binding sites for phospholipids, has been reported to anchor to PIP 2 where it is close to its substrates (Frohman and Morris, 1999).…”
Section: Toxins That Modulate Host Pld Activity Via Small Gtpasesmentioning
confidence: 99%
“…PI(3,4,5)P 3 may affect Ca 2ϩ release by increasing activity of the gamma isoform of PLC (PLC␥) either directly through binding to the pleckstrin homology domain (Falasca et al, 1998) and the Src homology (SH2) domain (Rameh et al, 1998), or indirectly after activating Bruton's kinase Btk (Li et al, 1997). PI(3,4,5)P 3 has been also implicated in the activation of small GTPase proteins from the Rho family, which in turn stimulate production of phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ] through activation of PI(4)5-kinase (Smith and Chang, 1989;Hartwig et al, 1995;Tolias et al, 1995;Ren et al, 1996;Carpenter et al, 1997;Rumenapp et al, 1998). Because PI3K uses PI(4,5)P 2 as a substrate, activation of PI3K may potentially have two opposing effects: it may cause a decrease in PI(4,5)P 2 levels (by using it as a substrate) and increase in PI(4,5)P 2 levels by modulating the activity of PI(4)5-kinase.…”
mentioning
confidence: 99%